Estrutura socioespacial de Maringá e os territórios de criminalidade - Casteletto, Hugo Santana (2014)
Urban violence has become the subject of numerous studies and research aimed at understanding, guide and discover the causes and consequences of numerous crimes, evidenced in a range whose data available indexes grow every year. Thus, we see that there is an association between crime (or modality of crime) areas and lower income classes, which leads to a misinterpretation in most jobs, since urban violence is not concerned her own, but rather a result of a number of factors, many of urban logistics and structural character, which segregate people in certain areas, either by real estate pressure and / or government, or both. This paper proposes a study of the relationship between the data of crimes (drug trafficking, simple and qualified thefts, robberies, assaults and murders) through the database of the 4th Battalion of the Military Police of Maringá; with data concerning the economic situation and infrastructure of each APOND (Area Weighting) of Maringá, these data obtained from Census of IBGE ( in 2010), so that we could see what the socio-structure of Maringá and what relationship exists between this structure and the formation of areas of crime in the city. Thus crimes by APOND 's ( Area Weighting ) and also indicators for the total population, per capita income, education, sanitation and other variables that helped us measure the position of each APOND were mapped, watching how violence in certain territory is associated with the socio-spatial characteristic of this territory. It was observed that property crimes such as burglaries and thefts occur mostly in APOND 's that have characteristics of high income and access to quality public service, as the territories that make up the downtown area as Zone 1 - zone 3; while crimes against person usually occur at peripheral sites where per capita income reported is relatively low and access to infrastructure and quality education are poor, such as Jardim Alvorada - Freedom and Diamond Garden - Northeast Rural Zone . Stand out from the Zone 1 - 3 Zone, Central APOND that occurs almost all types of crimes due to their unique features which makes it a place where you can find all social classes.